Loving and Loathing Physical Education: An Exploration of Students’ Beliefs - Robinson, Daniel B. (Alberta Journal of Educational Research, 2012)
This article describes a recent study that investigated the physical education (PE) beliefs of a particular population of students (i.e., female and male students in Grades 4 through 10 from a single school stream). Through their completion of an adapted survey, students (N = 506) were able to share their PE beliefs in relation to five separate subscales: PE Interest, PE Status, PE Connotations, PE Teachers, and PE Curriculum. Results suggest that grade and gender differences exist with respect to these subscales. Consequently, it is herein suggested that the discovery of such differences within this case study merits considerations for educational change, as well as continued and deeper inquiries into understanding the nature of PE beliefs for female and male students in various grade levels. Cet article décrit une étude récente qui a porté sur les croyances qu'a une population particulière d'élèves (c.-à-d. filles et garçons, de la 4e à la 10e année, d'une école à voie unique) par rapport à l'éducation physique. Par le biais d'une enquête adaptée, les élèves (N = 506) ont partagé leurs croyances sur l'éducation physique en fonction de cinq sous-échelles séparées: intérêt, statut, sens affectifs, enseignants et curriculum. Les résultats donnent à penser qu'il existe, par rapport à ces sous-échelles, des différences liées à l'année scolaire et au genre. On propose donc que les différences révélées par cette étude de cas méritent d'être considérées dans le contexte de changements pédagogiques et d'être étudiées en profondeur et à long terme pour comprendre la nature des croyances d'élèves, filles et garçons et à divers années scolaires, relatives à l'éducation physique.